Conjugated Dienyne‐Imides as Robust Precursors of 1‐Azatrienes for 6π Electrocyclizations to Furo[2, 3‐b]dihydropyridine Cores. Issue 19 (30th March 2018) - Wan, Yanjun; Zheng, Xuchun; Ma, Cheng
Abstract: A novel strategy to generate functionalized 1‐azatriene intermediates for 6π electrocyclizations was developed by using readily accessible dienyne‐imides and various terminal olefins under Pd II catalysis. Taking advantage of the sequential cooperation between preloaded and incorporated functional handles at 1, 3‐dien‐5‐yne skeletons, this method not only enables the selective generation of putative 1‐azatrienes but significantly accelerates their thermal 6π‐electrocyclic ring‐closure processes to a series of highly substituted furo[2, 3‐ b ]dihydropyridine derivatives in good yields. Abstract : Can you handle this? Oxypalladation‐initiated direct construction of furo[2, 3‐ b ]dihydropyridine cores via a putative 1‐azatriene intermediate was achieved from accessible dienyne‐imides through a handle‐relay strategy. The reaction proceeds under mild conditions and has a broad scope with respect to the terminal olefins.